IMPLEMENTASI KEBIJAKAN PERLINDUNGAN TENAGA KERJA INDONESIA (TKI) DI LUAR NEGERI PADA TAHAP PRA PENEMPATAN (Studi Kasus TKI Kota Palembang) - Doris Febriyanti; Isabella Isabella (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
Protection in the placement of Indonesian Workers (TKI) to enable them to obtain employment services quickly and easily while maintaining safety the physical, morals and dignity. In the implementation of the protection of Indonesia workers has been implemented but not optimal, the existing problems such as external communications executive agency is not going well, this is due to the lack of communication between BBLK and PPTKIS. Communications are not yet well established is also seen in the defense of the fulfillment of the rights of Indonesia workers because the insurance consortium has not been able to realize the obligation to pay compensation claims no later than seven (7) working days in accordance with applicable regulations. Social conditions that do not support the activities of pre placement protection of Indonesia workers, this is due to re-entry Indonesia workers objected to the payment of insurance premiums are charged at the time of manufacture KTKLN.The results showed that the implementation Protection of Indonesian Workers Abroad pre placement has been implemented, but not optimal. The constraints in the implementation of the implementation is the external communication, and social conditions that are less support protection of Indonesia workers.Keywords : Administration, Implementation, Protection of Indonesian Workers, Government Regulations on the Protection of Indonesian Workers.